Polymorphisme du microsatellite mitochondrial D310 dans la population Tunisienne - Yacoubi-Loueslati, Besma; Cherni, Lotfi; Frigi, Sabeh; Baroudi, Thouraya; El Gaaied, Amel Ben Ammar (Anthropologie, 2009)
In the present study, we have investigated the polymorphism of the mitochondrial microsatellite, situated between 303 and 315 bp positions, in a Tunisian population. The haplotype frequencies of this microsatellite were compared to those of other populations (Berbers from Sejnene and Takrouna, Bedouins, Portuguese, Italians, French, British, Spanish and Turkish). The obtained results reveal this mitochondrial microsatellite as a frequent hot spot of mononucleotide insertions. In fact, his polymorphic rate is superior to 93% in all analysed populations. The results showed that the two haplotypes 309.1 315.1 and 315.1 are the most frequent in all studied populations. The haplotype corresponding to the Cambridge Reference Sequence (CRS) is only detected in the Tunisian population, the Berbers from Sejnene and the British people.
Keywords: Polymorphism, Genetic; Tunisko; DNA, Mitochondrial; Tunisia; Humans; Data Interpretation, Statistical; lidé; mitochondriální DNA; polymorfismus genetický; interpretace statistických dat